Slovak nouns of short duration chvíľa, okamih vs. German Weile, Augenblick according to the parallel corpus - Daria Vashchenko (Vestnik Pravoslavnogo Svâto-Tihonovskogo Gumanitarnogo Universiteta: Seriâ III. Filologiâ)
The article examines the semantics of Slovak nouns with the meaning of short duration in relation to their German equivalents. The systems of temporal substances of short duration in Slovak and German demonstrate a significant degree of semantic and formal parallelism. Both languages have different indicators of exact and inaccurate time (minuta, sekunda vs chvila, okamih - Minute, Sekunde vs Weile, Augenblick). Similarly, in both languages, these nouns correlate both in terms of external form (minuta - Minute, sekunda - Sekunde, Weile - chvila: in the latter case, the Slovak noun is borrowed from German) and in terms of internal form (okamih – Augenblick: eyes blinking). It is revealed how the indicators of inaccurate time correlate with each other in terms of the real semantic content of tokens. The study was conducted on the material of the Slovak-German parallel corpus included in the Slovak National Corpus: the source language in the translations used is German. The main translational equivalent of the German Weile is indeed the Slovak chvila (for 2061 occurrences, 1288 cases are translated through chvila, and only 5 through okamih), while for Augenblick the situation is completely different: out of 5760 occurrences in 1471, the lexeme is translated as okamih, and 1952 – through chvila. The ways of transmitting Augenblick in different types of constructions are considered: prepositional, attributive, in constructions with particles and with verbs. At the same time, some of the constructions in the source language in translations are assigned to chvila, a small part is assigned to okamih, in a number of German constructions the number of equivalents of chvila - okamih is comparable. It is revealed that the semantics of Slovak nouns differs from their German correlates, since the Slovak chvila and okamih, in addition to the indefinite quantification of the time interval, have a number of additional connotations. In translations, chvila is oriented to the speaker's point of view, tends to situations of minimal tension or to those that do not involve drastic changes. In turn, okamih is focused on the point of view of an outside observer, as well as on situations of maximum tension - situations with sharp dynamics.